2008
DOI: 10.1111/j.1755-3768.2007.01142.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural analysis of collagen fibrils and proteoglycans in keratoconus

Abstract: . Purpose:  To investigate ultrastructural alterations in the distribution of collagen fibrils (CFs) and proteoglycans (PGs) in the keratoconus cornea. Methods:  Four normal corneas (donor age 24–75 years) and four severe and one mild keratoconus corneas (donor age 24–47 years) were fixed in 2.5% glutaraldehyde containing 0.05% cuprolinic blue dye for electron microscopy. Analyses were carried out on approximately 39 000 CF and 66 000 PG filaments in the anterior, middle and posterior stroma, using analySIS® s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 30 publications
3
59
0
4
Order By: Relevance
“…Although to some extent this may be due to a decrease in the corneal thickness and volume, it is mainly because of the altered structure of the stromal proteoglycans leading to lower lamellar adhesion and a lower shear modulus. 28,29 Significant and positive correlations were observed between CH, CRF, and corneal thickness as well as corneal volume in the normal, keratoconic, and crosslinked eyes. Similar findings were noted in the normal and keratoconic eyes in previous studies.…”
Section: Discussionmentioning
confidence: 83%
“…Although to some extent this may be due to a decrease in the corneal thickness and volume, it is mainly because of the altered structure of the stromal proteoglycans leading to lower lamellar adhesion and a lower shear modulus. 28,29 Significant and positive correlations were observed between CH, CRF, and corneal thickness as well as corneal volume in the normal, keratoconic, and crosslinked eyes. Similar findings were noted in the normal and keratoconic eyes in previous studies.…”
Section: Discussionmentioning
confidence: 83%
“…Using microfocus small angle scattering, Quantock et al (2007) showed that there was no systematic change in average fibril diameter as a function of depth. These results seem to conflict with those from electron microscopy reported above (Freund et al 1995) but are supported by more recent electron microscope measurements (Akhtar et al 2008). With microfocus wide angle scattering, Kamma-Lorger et al (2009) showed that the intermolecular spacing is relatively constant with tissue depth, indicating that there are no changes in the intrafibrillar water content, even when the bulk tissue hydration is changing.…”
Section: Corneal Lamellaementioning
confidence: 73%
“…These changes allow more contact between the collagen sheets and the proteoglycans, thus altering the stroma organization where alterations in interlamellar proteoglycans might contribute to slippage of the lamellae. 81 Meek et al, 82 using synchrotron X-ray scattering patterns, confirmed that a gross rearrangement of vertical and horizontal collagen lamellae occurs in keratoconus. Tissue degradation alone does not account for that systematic realignment of fibrils, and so the authors suggested that both slippage and remodeling have a role.…”
Section: Corneal Stroma Compositionmentioning
confidence: 85%